Upaya Preventif Keluarga Muslim terhadap Perilaku Seks Bebas (Penelitian pada Keluarga Muslim di Kota Bekasi) - Zarkasyi, Ezra Salwa Wahyu; Burhanuddin, Anas (UIN Sunan Gunung Dajti Bandung, 2023)
The causes of promiscuous sexual behavior are driven by various factors, including a lack of parental attention and control over children. Sex education in the family can be started from an early age and is carried out in simple language that is easy for children to understand. The aim of this research is to find out how much prevention efforts are made by families against free sexual behavior. This type of research is qualitative research using library research and field research methods. The results of this research show that religious education, discussion space, a healthy environment, social guidance, and parental example can be efforts to prevent free sexual behavior. Based on research, it can be concluded that the family has an important role in efforts to prevent promiscuous sexual behavior and that Islam does not ignore education related to sexuality.